Hydrological shifts in the Carpathian Basin: Climate change impacts on summer low-flows - Leščešen Igor (Geographica Pannonica, 2025)
To assess hydrological shifts in the Carpathian Basin, this study analyzes a 90-year summer minimum discharge dataset from 12 river stations. We reveal widespread, significant declines, with the most pronounced trends on the Danube showing an average decrease of (-8.9% per decade). Critically, we identify a systemic regime shift using Pettitt tests, with most changepoints occurring between 1968-1990. Self-Organizing Maps (SOMs) regionalize these trends into two clusters: a high-variability group (Danube/Sava) and a vulnerable, low-flow group (Tisza/Drava). These findings prove the region's growing drought vulnerability and highlight the urgent need for adaptive water management.